OPTIMIZATION AND QUALITY ANALYSIS OF BIO-BUTANOL PRODUCTION FROM SUGARCANE (Saccharum officinarum) BAGASSE HYDROLYSATE - Mukhtar, Ladan; Muhammad, M. L.; Zauro, S. A.; Rabah, A. B. (FUDMA JOURNAL OF SCIENCES, 2023)
Several companies are currently investigating in development for the production of Biobutanol. This research was concerned with Biobutanol production from ABE (Acetone, Butanol, and Ethanol) fermentation of sugarcane bagasse hydrolysate by Clostridium Perfringens. The sample was hydrolyzed with concentrated H2SO4 solution for 1 hour at 121oC. Response surface designed by optimizing the fermentation parameters (Time, Temperature, and pH) by the used media (C. Perfringens) showed the highest Biobutanol yield at temperature (350C), Time 48 (Hhs), and pH 6.0 with 163 cm3 which is exactly around 0.543(g/L) by converted to a gram per liter as mostly represented by many researchers. The produced Biobutanol from the sugarcane bagasse hydrolysate was characterized using FT-IR and GC-MS analysis. Conclusively this work revealed the importance of sugarcane bagasse as a good potential feedstock of Biobutanol.